Editorial Notes Vol.12 - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2018)
This is a happy moment for us to present Volume 12 Dhaulagiri Journal of Sociology and Anthropology to our respected readers. As this volume is the 12th, we have changed the size and layout of our Journal to make it standard size and reduce the paper waste during the printing process. We hope, you like it. Many people have contributed in different aspects of publishing this volume. We would also like to inform to our reader that this Journal is indexed in DOAJ and Ebscohost. The journal is also ranked by the Journal Publishing Practices Standard and awarded ’One Star’. We most work hard and sincerely to achieve higher ranking in coming volumes. We would like to offer our deep respect to Prof. Gregory Marskarnec who has contributed NPR. 10,000 (Ten Thouand Rupees) for printing of this volume. We are delighted with the work of wonderful reviewers, who supported and encouraged both authors and editorial team to improve and make appropriate judgement to the submitted papers. Without their rigorous work we would not have been able to bring this journal in this form. We would like to express our heartfelt thanks and sincere gratitude to all valuable reviewers: Rajendra Raj Timilsina, Janak Rai, Jiban Mani Paudel, Madhav Pokhrel, Ganga Ram Gautam, Dan Raj Regmi, Sushant Acharya, Sadruddin Bahadur Qutoshi, Prem Bahadur Bhandari, Jhakendra Bahadur Gharti, Jailab Rai, Madhu Giri, Anita Sherestha, Madhusudan Subedi, Man Bahadur Khattri, Rishikesh Pandey, Binod Pokhrel, Jaganath Adhikari, Madan Kumar Rimal, Dilli Raj Sharma, and Gyanu Chhetri. We must not forget to thank Sioux Cumming at INASP who has been very co-operative throughout the online publishing proceses. Similarly, we would like to express our sincere thanks to Netralal Neupane and Tika Ram Sapkota for their time and hard effort for proof reading.